Synthesis and Analysis of Nickel Oxide Nanoparticles from Red Hibiscus Plant and Evaluation of Its Antibacterial Properties - Rana Ismael Khaleel, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The presented research examines the environmentally friendly synthesis regarding nickel oxide (NiO) nanoparticles (NPs) for enhancing the properties related to the laser ablation-prepared nanomaterial. Red hibiscus is added as a plant extract to enhance the nanomaterial's properties as well as its antibacterial efficacy. NiO-NPs are created using a Nd: Yag pulsed laser with an 800 mJ wavelength and a wavelength of 1064 nm in a deionized water medium. At room temperature, optical absorbance spectra in the optical range (200-900 nm) have been examined. X-Ray Dispersive Spectroscopy, UV-Vis Spectroscopy, and Scanning Electron Microscopy (SEM) have been used in order to analyze the physical characteristics of NiO-NPs. The formation of high-purity NiO-NPs is demonstrated by EDX analysis. A few NiO-NPs have spherical forms and sizes between 44.66 nm and 134 nm, as seen in the SEM image. NiO-NPs' UV-Vis spectra showed that their absorption edge had a blueshift with an energy gap range (Eg) between 2.80 and 3.40eV. The antibacterial activity regarding NiO-NPs was tested in order to assess their biological efficacy. NiO-NPs were examined in vitro and activated as antibacterials to assess their toxicity. NiO-NPs showed good antibacterial activity against a few of the test organisms.
Keywords: Nickel oxide nanoparticles; red hibiscus; Nanoparticles characterization; Antibacterial activity